The Factors Affect Employee Loyalty with Job Satisfaction As A Mediator Variable To Generation Z During The Internship Program (Journal of Business and Management, 2022)
Human resources are one of the essential instruments in a company. Generation Z, which is predicted to dominate 20% of workplaces in 2025, brings an opportunity for companies to be able to adapt indirectly and adjust the business they are doing to keep up with existing developments, considering that Generation Z exist in the middle of technological developments. This study aimed to determine what factors influence job satisfaction, directly related to the level of employee loyalty of Institut Teknologi Bandung graduates belonging to Generation Z during their internship. This research is quantitative research using a questionnaire where what is measured is how training, working condition, internship benefits, and salary affect employee loyalty with a mediating variable, namely job satisfaction. The total number of respondents involved was 298, with 151 respondents who met the criteria. Training, internship benefit, and salary positively impact employee loyalty, and the work situation does not directly affect employee loyalty if company does not accommodate a proper working condition and job satisfaction.Keywords: Keywords: generation z, internship program, job satisfaction, employee loyalty.